Tussilago farfara Extracts Decrease Lung Injury in Fine Dust-Induced Mice by Inhibiting of Inflammatory Cytokine Levels, Neutrophil Accumulation, and Endothelial Dysfunction - Yun, Mi-Young; Baek, Won-Jin; Choi, Hwa-Jung (Archives of Pharmacy and Pharmaceutical Sciences, 2024)
Fine Dust (FD) in the respiratory air generates a variety of human disease issues throughout the earth. This study aimed to investigate whether (1) Tussilago farfara extracts (TF) decrease neutrophils accumulation, typical pathological features, and goblet cell hyperplasia in mice following exposure to fine dust (FD); (2) inflammatory cytokines result from FD exposure; and (3) asymmetric dimethyl-arginine (ADMA) and symmetric dimethyl-arginine (SDMA) levels in the mice following exposure to FD. Seven-week-old male Balb/c mice (n = 5/group) were instilled two times by intra-nasal-trachea (INT) injection for 3 days and 6 days to the mice four groups; normal, control, FD + dexamethasone (Dexa, positive control), and FD + TF groups. TF suspended in 0.5% carboxymethyl cellulose (CMC) was administered orally to the mice daily for 10 days (100 mg/kg). Neutrophil accumulation, typical pathological features, goblet cell hyperplasia, ADMA, and SDMA levels were assessed on day 10 in FD-induced mice. Results indicated FD significantly reduced neutrophil accumulation in BALF, typical pathological features containing goblet cell hyperplasia in lung tissues, and inflammatory cytokines [interleukin (IL)-17 and tumor necrosis factor-α (TNF-α), macrophage inflammatory protein-2 (MIP-2) and C-X-C motif chemokine 1 (CXCL-1)]. Furthermore, TF significantly decreased levels of elevated ADMA and SDMA by FD exposure. Collectively, TF decreased the counts of neutrophils in BALF, histological changes in lung tissues due to downstream secretion of inflammatory cytokines, and levels of ADMA and SDMA. Therefore, TF may be a potential therapeutics for treating FD-associated diseases.